Linguistic and Behaviour Interaction Analysis within Cognitive Infocommunications - Vogel, Carl; Esposito, Anna (My University, 2019)
Cognitive infocommunications is a discipline that examines the extensions of human cognitive capabilities that are assimilated within the concept of humanity. We argue that necessary (but not sufficient) conditions for the success of any candidate technology include solving problems within private and public spheres, in thought and communication. Exemplars such as emotion, gesture and language, as cognitive infocommunication technologies that have been assimilated, are examined. Implications for research programmes within cognitive infocommunications are addressed.
10th IEEE International Conference on Cognitive Infocommunications (CogInfoCom)
Keywords: Linguistics; Technological innovation; Clothing; Cognition; Decision making; Visualization; Digital Engagement; Behaviour Analysis; Computational Linguistics; Computational linguistics; computational linguistics; interaction analysis